2016
DOI: 10.1111/ped.12754
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new leukocyte parameters versus serum C‐reactive protein, procalcitonin, and interleukin‐6 in the diagnosis of neonatal sepsis

Abstract: Although the predictive value of leukocyte parameters including neutrophil and monocyte volume, conductivity, scattering and volume distribution width in the diagnosis of neonatal sepsis was lower than that of CRP, PC and IL-6, some of these new parameters may be useful in the differential diagnosis of newborn sepsis, along with the other screening tools. In particular, MNV seems to be the most useful parameter with the highest specificity; also, the importance of PC in the diagnosis of early onset sepsis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
(105 reference statements)
4
28
1
7
Order By: Relevance
“…In our study, at a cutoff 3 mg/L, CRP had sensitivity (70%), specificity (75.9%), PPV (75%) and NPV (71%) for diagnosing LOS. These results go to a great extent with those of Celik et al (2016)who reported 71.8% sensitivity, 76.3% specificity, 72.9% PPV and 72.5% NPV of CRP. Also, similar rates of sensitivity (76.9%, 72.6%) were reported by Hisamuddin et al (2015) and Kumar et al (2016) 128 respectively.…”
supporting
confidence: 77%
“…In our study, at a cutoff 3 mg/L, CRP had sensitivity (70%), specificity (75.9%), PPV (75%) and NPV (71%) for diagnosing LOS. These results go to a great extent with those of Celik et al (2016)who reported 71.8% sensitivity, 76.3% specificity, 72.9% PPV and 72.5% NPV of CRP. Also, similar rates of sensitivity (76.9%, 72.6%) were reported by Hisamuddin et al (2015) and Kumar et al (2016) 128 respectively.…”
supporting
confidence: 77%
“…40 Moreover, some new leukocyte parameters (neutrophil and monocyte volume, conductivity, scattering, and volume distribution width) may be useful in the differential diagnosis of newborn sepsis. 41 Macrophage cytokines, which are produced in response to microorganism antigens and which stimulate the release of acute-phase reactants and hence the host inflammatory immune reaction, are usually used in clinical practice as indicators of both EOS and LOS. 42 Moreover, serum markers, increasing earlier than changes in hematological parameters, play a pivotal role in the diagnostic process, allowing detection of sepsis and its severity, differentiation of bacterial from fungal and viral agents, and monitoring of response to therapy.…”
Section: Diagnosismentioning
confidence: 99%
“…Various markers are used for the prediction and detection of inflammation in clinical practice . Conventionally, WBC count, IT ratio, absolute leukocyte count, CRP, PCT and IL‐6 are used for accurate and timely diagnosis of infectious processes, especially in the sepsis of adults and newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Various complete blood count (CBC) parameters such as, white blood cell (WBC) count, immature/total leukocyte ratio (IT ratio), absolute leukocyte count together with procalcitonin (PCT) and acute phase reactants (C‐reactive protein [CRP] and interleukin‐6 [IL‐6]) are all used for the accurate and timely diagnosis of infectious processes . The role of these inflammatory markers and immune proteins in predicting preterm delivery has been investigated in several studies .…”
Section: Introductionmentioning
confidence: 99%